RETHINKING DIGITAL ACTIVISM AND TOLERANCE: A HABERMASIAN PERSPECTIVE FROM YIPC YOGYAKARTA - Armawi, Armaidy; Iman, Hafidz; Wibowo, Dany Chandra Purnama (Universitas Padjadjaran, 2025)
This study examines the digital activism of the Young Interfaith Peacemaker Community (YIPC) Yogyakarta in promoting tolerance, using Jurgen Habermas’s theory of deliberative democracy as an analytical framework. Adopting a qualitative research design with an intersubjective approach, the study involved three key informants who serve as YIPC facilitators. Data were collected through structured interviews, a review of Habermas’s theoretical works, and an analysis of public comments and interactions on YIPC’s Instagram account. Data analysis was conducted through curation, categorization, and thematic interpretation to explore conceptual dimensions, the formation of collective public opinion, the quality of rational debate, and the capacity to mediate between society and the state. The findings indicate that YIPC contributes to the development of a relatively inclusive digital public sphere and promotes pro-tolerance narratives through creative content, cross-community collaboration, and the empowerment of young content creators from marginalized groups. However, engagement with negative comments, while increasing visibility, occasionally generates less rational exchanges that weaken deliberative quality. Furthermore, YIPC’s role in mediating public policy remains limited, as its activities are primarily oriented toward education and community engagement rather than formal advocacy. These findings highlight both the potential and the limitations of digital activism in advancing deliberative democratic ideals within social media contexts.